Microstructure and Hardness of Cold Work Vanadis 6 Steel after Subzero Treatment at −140°C - Juraj Ďurica; Jana Ptačinová; Mária Hudáková; Martin Kusý; Peter Jurči (Advances in Materials Science and Engineering)
The microstructure, phase constitution, and hardness of Cr-V ledeburitic tool steel Vanadis 6 subjected to subzero treatment at −140°C and for different soaking times have been investigated. The light microscopy, scanning electron microscopy, and X-ray diffraction have been used for microstructural investigations. The hardness has been evaluated by the Vickers method. The obtained results assist to draw that subzero treatment reduces the retained austenite amount and increases the population density of carbides, compared to conventional heat treatment. The extent of decrease in the retained austenite amount makes around 85%, and the increase in population density of small globular carbides was approximately fivefold. High compressive stresses were identified in the retained austenite, and their values follow the increase in carbide count. This makes a serious support to the theory explaining the formation of “extra” carbides as a by-product of more complete martensitic transformation. As a result of the mentioned microstructural changes, the material hardness increased from 875 ± 16 HV 10 up to 954.6 ± 14 HV 10 for conventionally quenched and SZT steels, respectively.